British Economic Policy / 1960-74: Demand Management - Blackaby F.T. (Cambridge University Press, 1979)
This book covers public expenditure, budgetary policy, monetary policy, balance of payments policy and incomes policy. Introduction, Narrative - 1960-74, Public Expenditure, Budgetary Policy, Monetary Policy, Policies Aimed at Improving the Balance of Payments, Incomes Policy, General Appraisal, Selected Bibliography, Index.